(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study aims to analyse the role of the Government Section at Pulau Laut Kepulauan Sub-district Office, Kotabaru Regency, in the implementation of population administration and to identify the challenges encountered in its execution. A qualitative approach with a descriptive research design was employed in this study. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that the Government Section plays four strategic roles in population administration implementation: facilitator, mediator, motivator, and dynamist. As a facilitator, it provides information and assistance to the community. As a mediator, it coordinates with village governments and relevant agencies. As a motivator, it conducts socialisation to raise public awareness. As a dynamist, it drives service improvements through periodic data updates. However, several challenges were identified, including limited human resources, inadequate infrastructure, geographical constraints due to the archipelagic nature of the area, and low public awareness. These challenges often result in suboptimal service coverage and difficulties in accessing services for residents in remote islands. This study contributes to the public administration literature by providing empirical evidence regarding the role of sub-district governments in population administration implementation in archipelagic regions.. Keywords: population administration, public services, sub-district office, archipelagic region, Kotabaru